"I need to know": Recommendations on the Right to Information in Computer-Mediated Human Relations - Da Costa Nunes, Erik Henrique; Monteiro, Ingrid Teixeira (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2024: Anais do XXIII Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2024)
"Ubi societas, ibi jus" - where there is society, there is law. This maxim underscores the importance of law as an organizing and protecting element of human dignity, especially in the context of computing and digital product development. However, legal language is not always accessible, and developers are often not familiar with its complexities. Although there are seven heuristics for human-computer interactions based on consumer law, it is necessary to demonstrate their practical application in real situations. To this end, this paper presents an analysis of judicial decisions related to the right to information, focusing on the heuristic "All necessary information must be explicit to the user". Data from sentence aggregators from court search systems were used to conduct a content analysis of this information. The eleven recommendations resulting from this analysis emphasize the importance of translating legal principles for the computing community, recognizing their impact on computer-mediated relationships.